The treatment choices of abdominal aortic aneurysm patients in China in the era of value-based healthcare - Duan, Liren; Xin, Wei; Li, Shenli; Zhao, Lin; Xin, Shijie (Frontiers in Cardiovascular Medicine, 2022)
Background: Endovascular aneurysm repair (EVAR) is often seen as the first choice treatment for patients with abdominal aortic aneurysm (AAA), particularly high-risk patients, yet the long-term survival rate and improvement in quality of life are still unclear. In order to seek the value of EVAR to the entire healthcare field, we conducted a retrospective study to evaluate whether the improvement EVAR can truly bring tothe quality of medical care in the era of value-based healthcare. Methods: We included AAA patients who underwent surgical treatment in the Department of Vascular Surgery, First Hospital of China Medical University, from January 1, 2004, to December 31, 2019 and evaluated surgery procedure data, short-term and long-term mortality, complications, prognoses and medical costs. Results: We analysed 507 patients with AAA who underwent open repair (n = 232) or EVAR (n = 275) over a 15-year period. The operative time, blood loss, blood transfusion rate, and postoperative length of hospital stay of the EVAR group is significantly lower than which of the open repair group. Meanwhile, neither short-term nor long-term mortality rates shows significant differences between the two groups. On the other hand, the complication rate of the EVAR group was significantly higher than that of the open repair group. Lastly, the total cost of EVAR was significantly higher than that of open repair. Conclusion: Existing evidence suggests that EVAR improves neither short-term nor long-term survival rate compared with open surgery. In contrast, the complication rate and the reintervention rate in the EVAR group were higher than those in the open surgery group. Moreover, the cost of EVAR and that paid by medical insurance were higher than those for open surgery. For patients with a long-life expectancy, in order to ensure that patients receive appropriate and effective care, surgeons should choose a suitable method that considers both the quality of medical care as well as the expense accordingly.